Towards future physics and applications via two-dimensional material NEMS resonators. Issue 44 (5th November 2020) - Yildirim, Tanju; Zhang, Linglong; Neupane, Guru Prakash; Chen, Songsong; Zhang, Jiawei; Yan, Han; Hasan, Md Mehedi; Yoshikawa, Genki; Lu, Yuerui
Abstract : Two-dimensional materials (2Dm) offer a unique insight into the world of quantum mechanics including van der Waals (vdWs) interactions, exciton dynamics and various other nanoscale phenomena. Abstract : Two-dimensional materials (2Dm) offer a unique insight into the world of quantum mechanics including van der Waals (vdWs) interactions, exciton dynamics and various other nanoscale phenomena. 2Dm are a growing family consisting of graphene, hexagonal-Boron Nitride (h-BN), transition metal dichalcogenides (TMDs), monochalcogenides (MNs), black phosphorus (BP), MXenes and 2D organic crystals such as small molecules ( e.g., pentacene, C8 BTBT, perylene derivatives, etc. ) and polymers ( e.g., COF and MOF, etc. ). They exhibit unique mechanical, electrical, optical and optoelectronic properties that are highly enhanced as the surface to volume ratio increases, resulting from the transition of bulk to the few- to mono- layer limit. Such unique attributes include the manifestation of highly tuneable bandgap semiconductors, reduced dielectric screening, highly enhanced many body interactions, the ability to withstand high strains, ferromagnetism, piezoelectric and flexoelectric effects. Using 2Dm for mechanical resonators has become a promising field in nanoelectromechanical systems (NEMS) for applications involving sensors and condensed matter physics investigations. 2Dm NEMS resonators react with their environment, exhibit highly nonlinear behaviour from tension induced stiffening effects and couple different physics domains. The small size and high stiffness of these devices possess the potential of highly enhanced force sensitivities for measuring a wide variety of un-investigated physical forces. This review highlights current research in 2Dm NEMS resonators from fundamental physics and an applications standpoint, as well as presenting future possibilities using these devices.